2017
DOI: 10.1016/j.jjcc.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Giant aneurysms: A gender-specific complication of Kawasaki disease?

Abstract: We identified risk factors associated with an increased risk of giant CAA. The difference in variables between the giant CAA group and the other CAA subgroups suggests a separation between patients with the treatment-resistant giant CAA and the other IVIG-responsive patients, in which gender may be factored as a most relevant genetic trait. The increase in size during the first 2 months indicates the need for repeated echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In the present study, we found that male patients with CAA and the rs7251246 CC genotype had a significantly higher risk of thrombosis than children with the CT/TT genotype. This result may be attributed to male patients being more genetically susceptible to CAA and thrombotic events ( 35 , 36 ). As low-dose aspirin alone is not sufficient to prevent CAA thrombosis ( 37 39 ), the AHA recommends dual antiplatelet therapy as prophylaxis for patients at high risk ( 3 ); hence, dual antiplatelet therapy is recommended for male children with the CC genotype of rs7251246 to prevent thrombosis because the medical management of such patients depends on the judicious use of thromboprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that male patients with CAA and the rs7251246 CC genotype had a significantly higher risk of thrombosis than children with the CT/TT genotype. This result may be attributed to male patients being more genetically susceptible to CAA and thrombotic events ( 35 , 36 ). As low-dose aspirin alone is not sufficient to prevent CAA thrombosis ( 37 39 ), the AHA recommends dual antiplatelet therapy as prophylaxis for patients at high risk ( 3 ); hence, dual antiplatelet therapy is recommended for male children with the CC genotype of rs7251246 to prevent thrombosis because the medical management of such patients depends on the judicious use of thromboprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that sex plays an important role in the occurrence of CAA ( 31 , 32 ). Therefore, a separate statistical analysis was carried out on different sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, lots of studies evaluated the relationship between sexes and disease complications. Some of them resulted in a higher risk of complications in male patients [ 15 , 16 ]. Contrary to these, we found no statistically significant sex-specific risk for dilation and aneurysm.…”
Section: Discussionmentioning
confidence: 99%